Micronutrient status in bariatric surgery patients receiving postoperative supplementation per guidelines: Insights from a systematic review and meta‐analysis of longitudinal studies. (2nd May 2021) - Ha, Jane; Kwon, Yeongkeun; Kwon, Jin‐Won; Kim, Dohyang; Park, Shin‐Hoo; Hwang, Jinseub; Lee, Chang Min; Park, Sungsoo
Summary: The micronutrient status and optimal monitoring schedule after bariatric surgery have not been sufficiently assessed. This systematic review and meta‐analysis investigated the longitudinal changes in micronutrient status after bariatric surgery. PubMed, EMBASE, and Cochrane Library were searched for articles that measured preoperative and postoperative serum micronutrient levels in patients undergoing Roux‐en‐Y gastric bypass (RYGB) or sleeve gastrectomy (SG). Among guideline‐adherent studies, the longitudinal changes in micronutrient status were investigated using weighted mean difference (WMD) using a random‐effects model. Among the 82 included studies, the guideline adherence rates for micronutrient supplementation after bariatric surgery did not exceed 20%. In patients supplemented per guidelines, vitamin A significantly decreased after RYGB by −7.54 (95% confidence interval [CI], −10.16 to −4.92) μg/dl at 12–23 months, vitamin E decreased after RYGB by −2.35 (95% CI, −3.65 to −1.05) μg/dl at ≥24 months, and ferritin by −54.93 (95% CI, −77.19 to −32.67] μg/L at ≥24 months after SG, compared with baseline, with moderate level of evidence. Significant decreases in micronutrient levels at certain follow‐up intervals in studies with supplementation per guidelines need to be considered to establish a post‐bariatric micronutrient monitoring schedule for timely detection and management of micronutrient deficiencies.